Tailored nanostructured HDPE wax/UHMWPE reactor blends as additives for melt-processable all-polyethylene composites and in situ UHMWPE fiber reinforcement - Hofmann, Daniel Alexander; Kurek, Alexander; Thomann, Ralf; Schwabe, Jeremia; Mark, Stefan; Enders, Markus; Hees, Timo; Mülhaupt, Rolf (Macromolecules, 2017)
Tailored polyethylene reactor blend additives (RB) with ultrabroad bimodal molar mass distributions comprise nanophase-separated ultrahigh molar mass polyethylene (UHMWPE) uniformly dispersed in polyethylene wax. During injection molding of high-density polyethylene (HDPE) together with variable amounts of the nanophase-separated HDPE wax/UHMWPE (70/30) additive (RB30) flow-induced oriented crystallization affords shish-kebab fiber-like UHMWPE nanostructures accounting for efficient HDPE self-reinforcement. RB additives are readily prepared by ethylene polymerization on silica-supported two-site chromium catalysts which simultaneously produce HDPE wax together with disentangled nanoplatelet-like UHMWPE. The presence of HDPE wax is essential for lowering melt viscosity at high UHMWPE content. Since HDPE wax crystallizes onto extended-chain UHMWPE shish to form kebab structures, high HDPE wax content is tolerated without encountering emission problems and impairing mechanical properties as observed in the absence of UHMWPE. This in situ reinforcement substantially improves HDPE toughness/stiffness/strength balance as reflected by simultaneously increased Young’s modulus (+365%), tensile strength (+392%), and impact resistance (+197%). The performance of self-reinforced polyethylene (PE-SRC) is far superior to that of melt-blended UHMWPE/HDPE and the majority of PE nanocomposites. Neither hazardous UHMWPE nanoparticles nor alien inorganic nanofillers are required.